Nutritional value and chemical composition of quinoa leaves (Chenopodium quinoa Wild.) at different phenological stages - Edwin O. Baldeón; Augusto Sánchez-Pizarro; Ritva Repo-Carrasco-Valencia; José M. Barat; Raúl Grau; Attilio Israel Cadenillas-Martínez; Raúl Comettant-Rabanal (Manglar)
This study aimed to assess the phenological profile and nutritional characteristics of the leaves of four different quinoa varieties. The researchers analyzed the chemical composition, total phenolic compounds (TPC), and antioxidant capacity (AC) of quinoa leaves at various stages of growth. Two varieties, Blanca Junín and Blanca Criolla, displayed similar phenological profiles, while Pasankalla and Salcedo had earlier flowering stages. The study found that the early stages of quinoa leaves contained higher levels of protein, moisture, ash, magnesium, TPC, and AC. In contrast, the late stages had higher amounts of carbohydrates, calcium, and crude fiber. The third phenological stage showed the highest protein content, with Pasankalla and Blanca Junín having 36.00 g/100g and 42.44 g/100g, respectively. Salcedo reached this protein content at the second phenological stage, with 38.25 g/100g. Quinoa leaves were also found to be rich in potassium, magnesium, and calcium, with Blanca Junín and Pasankalla having the highest calcium levels in the sixth phenological stage. The second phenological stage consistently yielded the highest levels of TPC and AC in all quinoa varieties. Overall, this study highlights the nutritional value of quinoa leaves and suggests that they could be a promising plant-based protein ingredient.